Improving Early Childhood Health Literacy through a Smart Apps Creator Based PHBS Game - Rahayu, Aisah Karunia; Arzaqi, Roby Naufal; P, Aprida; Tianah, Iis; Umar, Tasya (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the implementation of Smart Apps Creator-based Clean and Healthy Living Behavior (PHBS) educational games in improving early childhood health literacy as a continuation of previous research that focused on media development and feasibility (Rahayu & Arzaqi, 2025). The research method used was a quasi-experiment with a one group pretest posttest design that was complemented by observation during implementation. The research subjects consisted of three children aged 57 years who were accompanied by students, with a five day implementation time which included one day of pretest, three days of game implementation, and one day of posttest. The aspects of health literacy studied include personal and environmental hygiene, healthy food, and physical activity. The research instruments were in the form of pretest, posttest, and observation sheets per PHBS game level, then analyzed descriptively, quantitatively and qualitatively. The results of the study showed that there was an increase in children's health literacy in all aspects of PHBS studied. The improvement was seen gradually through the results of daily observation which showed the development of independence, consistency, and accuracy of children's responses in completing each level of the game, and was strengthened by better posttest results than pretests. These findings show that PHBS educational games based on Smart Apps Creator are effectively used as an applicative and contextual health learning media for early childhood.